Strengthening Family Resilience For Micro, Small and Medium Enterprises - Agustina, Ike; Tatik, Tatik; Setiani, Novi; Divia, Helga Aurellia; Khairunnisa, Adinda Khansa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Work Family Conflict (WFC) is a pressure or imbalance between roles at work and roles in the family. Entrepreneurial families are very vulnerable to WFC, even more vulnerable than working families. Even though entrepreneurs are known to have flexible working hours, in reality entrepreneurs' working hours are unlimited. This service aims to provide assistance in strengthening the resilience of entrepreneurial families by focusing on managing stress and conflict in entrepreneurial families, building effective communication and balancing the roles of husband/wife of business actors in the family. The service partners are members of the Kaliurang Connection, which is an MSME community in Yogyakarta. The service method is training and counseling from a team of psychologists according to the participants' needs and problems.